A descriptive cross-sectional study of association between abnormal uterine bleeding and thyroid dysfunction - R. N., Thejashwini; V., Pruthvi Raj; Murthy, Sucheth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Abnormal uterine bleeding (AUB) is one of the most common gynecological presentation, accounting for at least 20% of all outpatient visits. Thyroid dysfunction has profound effect on the female reproductive system. Both hypothyroidism and hyperthyroidism are associated with untoward menstrual changes. This study aims to find the prevalence of thyroid dysfunction among patients with diagnosed AUB. Methods: A descriptive cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at General Hospital Jayanagar, Bengaluru. After taking ethical clearance from the Institutional Review Committee, the study was conducted on 100 patients with AUB satisfying the inclusion and exclusion criteria from November 2020 to May 2022. Thyroid function test was done in all patients by radioimmunoassay on an automated analyzer. Data was collected using a questionnaire which includes patient’s profile, pattern of AUB, examination and thyroid profile. Results: Out of 100 patients, it was found that 75% were euthyroid, 20% were hypothyroid, among which 15% had subclinical hypothyroidism and 5% had overt hypothyroidism and 5% were hyperthyroidism. The most common type of AUB was menorrhagia in 38%, followed by acyclical bleeding in 33%, polymenorrhoea in 11%, metrorrhagia in 8%, oligomenorrhoea in 7%, and hypomenorrhea in 3%. The maximum number of patients were between 30-40 years. Conclusions: Thyroid dysfunction is one of the important causes of AUB with hypothyroidism being the most common type in patients with menorrhagia. It was reported that their symptoms improved with thyroid medication.